ASSESSMENT OF GESTATIONAL DIABETES MELLITUS IN A TERTIARY CARE HOSPITAL, BIHAR: A CROSS-SECTIONAL STUDY. - kumari, Nilu (Student’s Journal of Health Research Africa, 2024)
Background Gestational diabetes mellitus (GDM) is a prevalent pregnancy condition involving intolerance of glucose, leading to significant maternal and fetal health risks. The purpose of the study is to assess glycemic management and pregnancy outcomes in GDM-diagnosed pregnant women. Methods A prospective observational study was conducted involving 80 pregnant women, with 40 diagnosed with GDM and 40 serving as controls. Participants underwent glucose challenge tests (GCT) and oral glucose tolerance tests (OGTT) for screening. Women diagnosed with GDM were prescribed a diabetic diet based on BMI and, if necessary, insulin therapy. Data on mother and fetus outcomes were gathered and analyzed using SPSS software. A p-value < 0.05 was deemed statistically relevant. Results The average age was 29.5 years (± 4.3). The GDM group showed notably higher fasting (99.2 ± 11.3 mg/dl) and postprandial glucose levels (136.8 ± 14.7 mg/dl) compared to the control group (84.7 ± 8.9 mg/dl and 112.3 ± 10.2 mg/dl, respectively; p < 0.001). Thirty percent of the GDM group required insulin therapy. Cesarean section rates were greater in the GDM group (45% vs. 25%, p = 0.05). Adverse fetal outcomes, including macrosomia (20% vs. 5%, p = 0.04), neonatal hypoglycemia (15% vs. 2.5%, p = 0.04), and respiratory distress (10% vs. 0%, p = 0.05), were more frequent in the GDM group. Conclusion The study highlights the significant impact of GDM on mother and newborn health, with higher rates of Cesarean sections and adverse fetal outcomes in the GDM group. Effective glycemic control through dietary management and insulin therapy is crucial for improving pregnancy outcomes. Recommendations There is a need for stringent glucose monitoring and personalized treatment plans for pregnant women with GDM. Further research should focus on optimizing management strategies and exploring new interventions to reduce the risks associated with GDM.